Healthcare waste management as a tool for human health protection: a mini review (Research, Society and Development, 2022)
Healthcare wastes are generated by human or animal healthcare facilities. A small portion of these wastes are considered dangerous. However, accidents generated by incorrect waste management is a reality around the world. Accidents happen in different management stages, from the waste generation to its final destination, if waste is not properly managed. Therefore, this work aimed to discuss the possible problems related to the incorrect healthcare waste management, focusing on public health. This mini-review discussed some of the ways in which waste management can favor the preservation of public health and the environment, through steps such as minimization, segregation and recycling.